CNS Depressant and Antiepileptic Activities of the Methanol Extract of the Leaves of Ipomoea Aquatica Forsk - Dhanasekaran Sivaraman; Palayan Muralidaran (E-Journal of Chemistry)
The central nervous system (CNS) depressant and antiepileptic activities of the methanol extract of the leaves of Ipomoea aquatica Forsk (IAF) were investigated on various animal models including pentobarbitone sleeping time and hole-board exploratory behavior for sedation tests and strychnine, picrotoxin and pentylenetetrazole-induced convulsions in mice. IAF (200 and 400 mg/kg, p.o.), like chlorpromazine HCl (1 mg/kg, i.m.), produced a dose-dependent prolongation of pentobarbitone sleeping time and suppression of exploratory behavior. IAF (200 and 400 mg/kg) produced dose-dependent and signiﬁcant increases in onset to clonic and tonic convulsions and at 400 mg/kg, showed complete protection against seizures induced by strychnine and picrotoxin but not with pentylenetetrazole. Acute oral toxicity test, up to 14 days, did not produce any visible signs of toxicity. These results suggest that potentially antiepileptic compounds are present in leaf extract of IAF that deserve the study of their identity and mechanism of action.